Assessment of Lyme disease risk by using the ecological risk index in the parks of Belgrade - Krstić, Milena; Stajković, Novica; Bokonjić, Dubravko; Lazić, Srdjan (Vojnosanitetski pregled, 2017)
Background/Aim. Factors determining the risk of Lyme disease (LD) may be followed in terms of the type of habitat. The evaluation of the risk of Borrelia burgdorferi (B. burgdorferi) transmission in humans on Ixodes ricinus (I. ricinus) tick habitats is done by means of the ecological risk index, which determines the tick habitat, abundance and infection rate. The aim of this paper was to determine the value of ecological risk index (potential and actual risk – PR and AR) on green areas in 9 pаrks in Belgrade and establish the correlation of this index with tick bites in humans. Methods. Ticks were collected in parks by means of the flag hour method and examined for the presence of LD cause in dark-field microscopic analysis. Point values were assigned to certain parameters and potential and actual risk index evaluated for each habitat. The data on tick bites from the surveyed habitats were obtained from the Protocol of patients bitten by ticks of the Sector for Preventive Medicine, Institute of Epidemiology, Military Medical Academy in Belgrade. Analysis of variance (ANOVA), Tukey test and Pearson´s coefficient were used in statistical analysis of data. Results. In Belgrade´s park habitats a high PR of B. burgdorferi transmission was determined, while AR for 4 habitats was categorised as PR, and limited for other 5 habitats. Statistically, in terms of AR values the following habitats were significantly different (p
Keywords: ticks; risk assessment; borelia burgdorferi; disease vectors; serbia